About this volume: the monograph of Hypericum by Norman Robson - Carine, Mark A.; Christenhusz, Maarten J. M. (Phytotaxa, 2013)
With about 470 species Hypericum Linnaeus (1753) is one of the 100 large angiosperm genera that collectively comprise an estimated 22% of angiosperm diversity (Scotland, 2000). The size of such genera means that complete monographic treatments to account for species diversity are time-consuming, costly and labour-intensive. Consequently, the species-level taxonomy of most such groups is poorly known (Frodin 2004, Scotland & Sanderson 2004). This presents a substantial barrier both to the goal of completing the global inventory and to understanding the evolution of the diversity they contain.